Paradygmat produkcyjno-konsumpcyjno-mediacyjny - Lees-Maffei, Grace (Artium Quaestiones, 2021)
This is a translation of a seminal, historiographic and methodological article by Grace Lees-Maffei concerning design history as an area of study and an academic discipline,originally published as: “The Production-Consumption-Mediation Paradigm” in: „Journal of Design History” 2009, 22(4), p. 351–376. Translated by Filip Lipiński